Obstructive jaundice secondary to chronic midgut volvulus. Issue 5 (May 1983) - Spitz, L; Orr, J D; Harries, J T
Abstract : A case of progressive extrahepatic biliary obstruction due to chronic midgut volvulus secondary to malrotation in a 5-month-old girl is presented. The obstruction to the bile duct was relieved after correction of the malrotation and division of the obstructing bands.